PERAN KEPEMIMPINAN PENDIDIKAN MADRASAH DALAM PENGELOLAAN KEARSIPAN DIGITAL DI PERPUSTAKAAN - Anggun Nur Syifa; Imay Rhotul Triwidowati; Nayla Trisasta Ashfiya; Siswadi (STKIP Subang, 2026)
This study aims to analyze the role of educational leadership in madrasahs in managing digital archives in libraries. The development of information technology has encouraged the transformation of archival management from conventional systems to digital systems that are more efficient, accurate, and accessible. However, the implementation of digital archiving in madrasah environments still faces various challenges, such as limited human resources, infrastructure, and lack of policy support. In this context, educational leadership plays a strategic role in directing, managing, and optimizing digital archival systems in libraries. This study uses a qualitative approach with literature study and descriptive analysis methods. The results show that the leadership of madrasah principals plays an important role in determining the success of digital archive management through policy formulation, improving the competence of library staff, and providing technology-based facilities and infrastructure. Therefore, effective educational leadership can improve the quality of digital archival management and support more modern and accountable library services.